Integrin α6-Targeted Molecular Imaging of Central Nervous System Leukemia in Mice - Zhang, Wenbiao; Li, Yongjiang; Chen, Guanjun; Yang, Xiaochun; Hu, Junfeng; Zhang, Xiaofei; Feng, Guokai; Wang, Hua (Frontiers in Bioengineering and Biotechnology, 2022)
Central nervous system leukemia (CNS-L), caused by the leukemic cells infiltrating into the meninges or brain parenchyma, remains the main reason of disease relapse. Currently, it is hard to detect CNS-L accurately by clinical available imaging models due to relatively low amount of tumor cells, confined blood supply and the inferior glucose metabolism intensity. Recently, integrin α6-laminin interactions have been identified to mediate CNS-L, which suggests that integrin α6 may be a promising molecular imaging target for the detection of CNS-L. The acute lymphoblastic leukaemia (ALL) cell line NALM6 stabled transfected with Luciferase were used to establish the CNS-L mouse model. CNS-L bearing mice were monitored and confirmed by the bioluminescence imaging. Three our previously developed integrin α6 targeted peptide based molecular imaging agents, Cy5-S5 for near-infrared fluorescence (NIRF), Gd-S5 for magnetic resonance (MR) and 18F-S5 for positron emission tomography (PET) imaging, were employed for the molecular imaging of these CNS-L bearing mice. Bioluminescence imaging showed local intensive signal in the heads among CNS-L bearing mice, meanwhile Cy5-S5/NIRF imaging produced intensive fluorescence intensity in the same head regions. Moreover, Gd-S5/MR imaging generated superior MR signal enhancement at the site of meninges, which located between the skull bone and brain parenchyma. Comparatively, MR imaging with the clinically available MR enhancer Gd-DTPA did not produce distinguishable MR signal in the same head regions. Additionally, the 18F-S5/PET imaging also generated focal radio-concentration at the same head regions, which generated nearly 5-times tumor-to-background ratio compared to the clinically available PET radiotracer 18F-FDG. Finally, pathological examination identified layer-displayed leukemic cells in the superficial part of brain parenchyma tissue, and immunohistochemical staining confirmed the overexpression of integrin α6 within the lesion. These findings suggest the potential application of these integrin α6-targeted molecular imaging agents for the accurate detection of CNS-L.